Pemanfaatan Jantung Pisang (Musa Paradisiaca) Sebagai Bahan Pangan Alternatif (International Forum of Researchers and Lecturers, 2025)
Banana blossoms are a part of banana plants (Musa paradisiaca) that are often underutilized and considered agricultural waste. However, banana blossoms have significant potential as an alternative food source with high nutritional value. This study aims to analyze the nutritional content of banana blossoms, develop optimal processing methods, and evaluate their economic potential. The methods used include laboratory experimental approaches for proximate analysis, organoleptic tests for sensory evaluation, and cost analysis calculations for economic assessment.The research findings indicate that banana blossoms contain high fiber (5.7 g/100g), moderate protein (1.6 g/100g), low fat (0.3 g/100g), and are rich in calcium (50 mg/100g), potassium (553 mg/100g), and antioxidants. The optimal processing method was a combination of initial boiling followed by stir-frying, which preserved 87% of the nutrients and produced the best sensory profile. Product development, including banana blossom floss, chips, and flour, demonstrated high consumer acceptance (>70%) with a profit margin ranging from 35-55%.This study concludes that banana blossoms have great potential as a sustainable alternative food source with high nutritional value and promising economic prospects. Utilizing banana blossoms can contribute to food security, the diversification of functional food products, and the empowerment of community-based economic development. Therefore, further efforts to enhance the utilization of banana blossoms should be encouraged to support the sustainability of the food and economic sectors.